2013
DOI: 10.1038/cdd.2013.112
|View full text |Cite
|
Sign up to set email alerts
|

TNFR1 determines progression of chronic liver injury in the IKKγ/Nemo genetic model

Abstract: Death receptor-mediated hepatocyte apoptosis is implicated in a wide range of liver diseases including viral and alcoholic hepatitis, ischemia/reperfusion injury, fulminant hepatic failure, cholestatic liver injury, as well as cancer. Deletion of NF-jB essential modulator in hepatocytes (IKKc/Nemo) causes spontaneous progression of TNF-mediated chronic hepatitis to hepatocellular carcinoma (HCC). Thus, we analyzed the role of death receptors including TNFR1 and TRAIL in the regulation of cell death and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 46 publications
(45 reference statements)
0
33
1
Order By: Relevance
“…Consistent with our results using LPC-specific TRAIL-R knockout, a recent study showed that systemic TRAIL-R deficiency could not prevent hepatocyte apoptosis, hepatitis and HCC in NEMO LPC-KO mice. 29 In the same study, systemic TNFR1 deficiency could significantly protect NEMO LPC-KO mice from hepatocyte apoptosis and compensatory proliferation, liver inflammation and fibrosis, and also inhibited liver tumour progression. It is therefore surprising that LPC-specific knockout of TNFR1, and even in combination with Fas and TRAIL-R, failed to protect NEMO LPC-KO mice from hepatocyte death, hepatitis and HCC development.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Consistent with our results using LPC-specific TRAIL-R knockout, a recent study showed that systemic TRAIL-R deficiency could not prevent hepatocyte apoptosis, hepatitis and HCC in NEMO LPC-KO mice. 29 In the same study, systemic TNFR1 deficiency could significantly protect NEMO LPC-KO mice from hepatocyte apoptosis and compensatory proliferation, liver inflammation and fibrosis, and also inhibited liver tumour progression. It is therefore surprising that LPC-specific knockout of TNFR1, and even in combination with Fas and TRAIL-R, failed to protect NEMO LPC-KO mice from hepatocyte death, hepatitis and HCC development.…”
Section: Discussionmentioning
confidence: 85%
“…It is therefore surprising that LPC-specific knockout of TNFR1, and even in combination with Fas and TRAIL-R, failed to protect NEMO LPC-KO mice from hepatocyte death, hepatitis and HCC development. Considering that haematopoietic chimera experiments suggested that TNFR1 deficiency in radioresistant cells prevents hepatitis and HCC in NEMO LPC-KO mice, 29 one possibility is that TNFR1 acts in liver stromal cells that are not targeted by the Alfp-Cre transgene, such as stellate cells or endothelial cells to mediate hepatocyte apoptosis and liver tumour progression. However, in that case TNFR1 signalling must be driven by a ligand other than TNF as TNF deficiency failed to prevent or ameliorate liver damage and HCC development in NEMO LPC-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have described that TNF-R1 deletion in NEMO Dhepa livers rescues hepatocyte injury and apoptosis (14). Fig.…”
Section: /P21mentioning
confidence: 99%
“…In most cell types. The biological effects of TNF in the liver have been largely attributed to signaling through TNFR1 [19], although the involvement of both TNFR1 and TNFR2 in cell death signaling has been shown in models of liver injury [12,20]. The intracellular domains of TNFR1 and TNFR2 are devoid of intrinsic kinase activity and therefore depend on homophilic protein-protein interactions b etween motifs of approximately 80 amino acids for the initiation of cell signaling [14].…”
Section: Tnf: Molecules and Structurementioning
confidence: 99%
“…This process involves phosphorylation of RIP1/3 and the formation of a signaling complex called the necroptosome [37,38]. Loss of NF-κB function promotes TNF-driven inflammation and hepatic injury which can be diminished by deletion of TNFR1 [19]. In hepatocytes, loss of cFLIP increases the susceptibility to apoptosis [39], while the loss of caspase 8 promotes nonapoptotic hepatocyte death [40].…”
Section: Tnf Signaling Pathways Signal Transduction By Tnfr1mentioning
confidence: 99%